The association between one’s social life and symptoms of prolonged grief following a traumatic loss: an ecological momentary assessment study - Philippa Specker; Justina Pociūnaitė-Ott; Ariela Lev Rosenblum; Sofia Marcolini; Pascale Waschnig; Christopher Magoon; Annie-Lori Joseph; Lieke C. J. Nijborg; Xi Pan; Lonneke I. M. Lenferink (European Journal of Psychotraumatology)
Background: A strong social safety net may play a key role in protecting people from developing prolonged grief disorder (PGD) after a traumatic loss. This has mainly been investigated cross-sectionally, whereby people usually report on their social life and PGD reactions during the past month. However, retrospectively recalling experiences is prone to recall bias.Objective: As such, we investigated the associations between pleasantness of social interactions and PGD reactions in traumatically bereaved people using Ecological Momentary Assessment (EMA).Methods: People whose loved one died due to homicide, suicide, or accident at least 12 months earlier (N = 36, 78% women, Mage = 56, 47% met PGD criteria) received smartphone-based surveys five times per day for two weeks. Surveys included questions about PGD intensity (e.g. ‘In the past 3 hours, did you yearn for your loved one?’ 0 = not at all, 6 = extremely) and their quality of social life (e.g. ‘In the past 3 hours, how did you find being with others?’ 0 = very unpleasant, 6 = very pleasant). Linear mixed models were used.Results: Based on 2520 measurement occasions, we found that when a person enjoyed their social life more than usual, they grieved less (B = −0.141, SE = 0.020, p < .001). However, whether a person’s social life was more or less pleasant than their peers was not related to their PGD levels.Conclusions: This EMA study highlights the importance of accounting for individual variability in grief reactions after loss and highlights the potential utility of strengthening one’s social safety net as a way to reduce the burden of PGD.